Perancangan Interior Hotel Resort Pines Garden di Tretes, Pasuruan, Jawa Timur - Yussy Riadi (Intra, 2015)
Resort is a hotel which is usually located outside the city , in the mountains , on the beach , at the edge of the lake or in the area where the vacation / recreation which provide facility to people who are on vacation in a relatively long period of time . Hotel Resort Pines Garden is a three-star hotel with 31 guest rooms that are close to the waterfall tourist rides Kakek Bodo . Interior design hotel resort Pines Garden aims to improve the image and quality of the hotel so as to increase the number of visitors (commercial). particularly attract the tourists who visit Tretes tourist areas , or for those who simply want a vacation / recreation. The design concept of " Warm Garden " combines elements of nature ( garden ) and modern feel of the room with warm (warm ) , according to the climatic conditions in Tretes cold . Application concept of taking wood materials representing rustic style with a predominance of brown color ( warm concept ) , as well as the use of the color green as accent and decorative elements of the garden , such as garden lights, fountains and greenery to represent the concept of garden. Expected with good interior design can provide new and different experiences for visitors / guests the hotel , and even raised the hotel 's image in the eyes of the tourists / visitors .